PÉRDIDA AUDITIVA INDUCIDA POR RUIDO EVALUADA EN ODONTÓLOGOS DOCENTES DE LAS CLÍNICAS ODONTOLÓGICAS DE LA UNIVERSIDAD SANTO TOMAS (2018)
Objective: To identify the degree of auditory loss in educational dentist of the Santo Tomas University dental clinics according to the audiology qualification of the occupational scales of Larsen and ELI.Materials and Methods: A observational descriptive study of prevalence was made; the universe was 32 dentists and the sample was 27 dentists, selected by voluntary sampling. The relation of the presence of PAIR with each variable was analyzed by Chi2, Student´s t and Fisher Exact test; a significance level was considered α = 0.05. The exit variables were the presence of loss audition according to ELI and Larsen for both ears and like explanations variables the related ones to the sociodemographics and clinical aspects.Results: The prevalence of PAIR according to the qualification of the ELI scale was in the left ear in a 62.9%; the women demonstrated noticeable alteration at this level. In the scale Larsen the right ear report 88.9% of prevalence being the men who presented/displayed greater alteration.Conclusion: According to the valuation of the ELI scale the women demonstrate the beginning of the auditory alteration in the frequency of 4000 Hertz and in the men there is commitment of the acute and conversational frequencies being well-known the lost evolution of the auditory one.